Yamabe Solitons On (LCS)n -Manifolds. Issue 2 (2nd July 2020) - Roy, Soumendu; Dey, Santu; Bhattacharyya, Arindam
Abstract: The object of the present paper is to study some properties of ( LCS ) n -manifolds whose metric is Yamabe soliton. We establish some characterization of ( LCS ) n -manifolds when the soliton becomes steady. Next we have studied some certain curvature conditions of ( LCS ) n -manifolds admitting Yamabe solitons. Lastly we construct a 3-dimensional ( LCS ) n -manifold satisfying the results.